If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5hm = h + 28k Solving 5hm = h + 28k Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-1h' to each side of the equation. -1h + 5hm = h + -1h + 28k Combine like terms: h + -1h = 0 -1h + 5hm = 0 + 28k -1h + 5hm = 28k Combine like terms: 28k + -28k = 0 -1h + 5hm + -28k = 0 The solution to this equation could not be determined.
| 4z+10-2z=6+z+8 | | x(2x+7)-5=(x+4)(5-x) | | 6x^2+27x-15=0 | | x+y=85 | | 5/9(F-32)= | | (4.6)(-2.25)= | | A=7+3x(5+49*7) | | 6n+8=3n+36 | | (-1.2)(-3.1)= | | x+x+20+4x-33=677 | | 4a+5+6a= | | (5x-8)(4-3x)+x(4-x)=0 | | -21(3)= | | 6+2p-4=6p+16-2p | | 4(-8)= | | 4+2x=x-9 | | 4.8-10= | | a+(17+a)+(4a-35)=900 | | -9(z-1)=5-8z | | 1.5-9.6= | | 2+3a= | | 5z+3z=7z+3 | | -5X^2+5X-4=-X^2-7X+5 | | p=76l+128w | | -5(4x-2)+12x=-6 | | x+x+350000=550000000 | | -21-4= | | 5x^2-13x+2=0 | | 8-(-4)= | | -14-(-2)= | | -8a=13 | | -5+(-11)= |